A new Maxwell model and its application in researching the compressive creep properties of recombinant bamboo - Shanshan Shen; Qifeng Gao; Xiaolin Gong; Songsong Sun; Jiahong Fu (PLoS ONE, 2025)
Fiber-reinforced composite materials manufactured through gluing techniques, such as recombinant bamboo, usually exhibit obvious creep behavior during service. In this work, the compressive creep performance of the recombinant bamboo was selected as the research object. First, a compressive fracture experiment was proposed to determine the compressive strength of the material. Second, different groups of compressive creep experiments were carried out on four samples under several stress levels. Finally, the new Maxwell model proposed in this paper was selected for analyzing the creep performance of the material. The main conclusion drawn from the research is that, compared with traditional commonly used models (Kelvin and Burgers), the newly proposed Maxwell model, which is based on the theory of the variable-order fractional derivative, can more accurately simulate the compressive strain creep growth property with relatively fewer parameters, and the stress level effect on the main model parameters can be accurately determined, which makes this approach valuable for actual engineering applications.